Use of Androgen Deprivation Therapy for Metastatic Prostate Cancer in Older Men - Keating, Nancy L. (2008)
PURPOSE: Uncertainty exists about the ideal timing for initiation of androgen deprivation therapy for men with metastatic prostate cancer. We assessed factors associated with early or delayed androgen deprivation therapy among men diagnosed with metastatic prostate cancer and assessed the relationship between this therapy and overall survival. PATIENTS AND METHODS: We studied a population-based cohort of American men aged ≥66 years diagnosed with metastatic prostate cancer during 1992–2002 and followed through 2003. We assessed receipt of androgen deprivation therapy early (within 4 months of diagnosis), delayed (after 4 months), or not at all, used multinomial logistic regression to identify factors associated with treatment, and used Cox proportional hazards models to assess whether treatment was associated with survival. RESULTS: Overall, 69.5% of men received early hormonal therapy and 7.3% delayed. Adjusted rates of early therapy were lower for black vs. white men (58.3% vs. 71.0%) and adjusted rates of delayed use were higher for black vs. white men (12.7% vs. 6.2%). Receipt of androgen deprivation therapy was associated with improved survival (adjusted HR=.69 95% CI .66–.73). The benefit for early treatment did not differ from delayed treatment (P=.58) CONCLUSIONS: A large minority of men with metastatic prostate cancer, particularly black men, receive delayed or no hormonal therapy. Receipt of early or delayed hormonal therapy was associated with similarly prolonged survival. After controlling for patient and tumor characteristics, survival did not differ by race, and receipt of hormonal therapy did not contribute to racial differences in survival.